3D bioprinted graphene oxide-incorporated matrix for promoting chondrogenic differentiation of human bone marrow mesenchymal stem cells - Zhou, Xuan; Nowicki, Margaret; Cui, Haitao; Zhu, Wei; Fang, Xiuqi; Miao, Shida; Lee, Se-Jun; Keidar, Michael; Zhang, Lijie Grace (Carbon (New York), 2017)
Articular cartilage repair and regeneration are a challenging problem worldwide due to the extremely weak inherent regenerative capacity of cartilaginous tissue. As an emerging tissue engineering scaffold fabrication technology, 3D bioprinting has shown great promise in fabricating customizable artificial tissue matrices with hierarchical structures. The goal of the present study is to investigate 3D bioprinted graphene oxide (GO)-doped gelatin–based scaffolds for promoting chondrogenic differentiation of human bone marrow mesenchymal stem cells (MSCs). In the current study, GO-gelatin methacrylate (GelMA)–poly (ethylene glycol) diacrylate (PEGDA) was prepared as a biocompatible photopolymerizable bioink. GO, a multifunctional carbon based nanomaterial, was incorporated into the bioink for promoting chondrogenic differentiation. Finally, the 3D printed GelMA-PEGDA-GO scaffold with hierarchical structures was fabricated via our novel table-top stereolithography-based printer. Results showed that GelMA-PEGDA-GO scaffolds greatly promoted the glycosaminoglycan, and collagen levels after GO induced chondrogenic differentiation of hMSCs. Moreover, the Collagen II, SOX 9, and Aggrecan gene expressions associated with chondrogenesis were greatly promoted on the scaffolds. This study demonstrated that customizable 3D printed GelMA-PEGDA-GO scaffolds are excellent candidates for promoting chondrogenic differentiation of hMSCs and are therefore promising candidates for future cartilage regenerative medicine applications. [Display omitted]